THE INFLUENCE OF BRAND IMAGE AND PROMOTIONAL MIX TOWARD USERS’ REPURCHASE INTENTION OF TELECOMMUNICATION PROVIDER (A CASE STUDY OF SMARTFREN USERS IN UNIVERSITY OF BRAWIJAYA, INDONESIA) - Radya Mahardika; Noermi jati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Repurchase intention is one factor that is important for marketers. Marketers already did many strategies in order to keeping the repurchase intention of their customers. The strategies that had been used are maximizing the company good brand image and maximizing their promotional mix. This study aimed to know how significant the influence of brand image and promotional mix toward the repurchase intention of Smartfren user in University of Brawijaya partially. The data analysis on this study uses multiple linear regression methods with 65 Smartfren users as respondent. The sampling technique uses purposive sampling. Validity and reliability test is used in this study with classical assumption test which is normality test, heteroscedasticity test, and multicollinearity test. The result of this study shows that brand image (X1) and promotional mix (X2) has significant influence toward the repurchase intention of Smartfren user in University of Brawijaya partially. By maintaining one of the aspects of brand image which is the uniqueness, Smartfren user will find it difficult to switch to another brands and Smartfren will be favorable. Keywords: Smartfren, brand image, promotional mix, repurchase intention